Effect of Perineal Urethrostomy on the Length of the Urethra of the Cat: A Cadaveric Study - Anna Shipov; Inbar Israeli; Jean-Philippe Billet; Yoav Adam; Joshua Milgram (Animals, 2023)
Perineal urethrostomy in cats is indicated for urethral pathologies located distal to the bulbourethral glands. The description of the bulbourethral glands as the cranial landmark when performing a PU is based on the increased urethral diameter at this location, rather than on an anatomical limitation. This suggests that urethral pathologies cranial to the bulbourethral glands could potentially be treated with PU. At present, the extent to which the pelvic urethra can be mobilized is unknown. Characterization and quantification of the effect of PU on the pelvic urethra is required prior to attempting to define the location of the pelvic urethra, cranial to the bulbourethral glands, which can be exteriorized when performing a PU. Our aim was to characterize and quantify the effect of performing a PU on the location and length of the pelvic urethra. Methods: Ten male feline cadavers were used, and four markers were placed on the pelvic urethra via a ventral approach to the peritoneal and pelvic cavities. Two orthogonal radiographic views were acquired prior and subsequent to performing a PU. The distance of each marker to a predefined landmark/origin and the distances of the markers relative to each other were measured on all radiographs. Results: PU resulted in significant caudal translation of the markers relative to the predefined landmark on all radiographic views; however, PU did not result in a significant change in the distances between the markers. Conclusions: Performing a PU results in caudal translation and minimal stretching of the mobilized pelvic urethra.